STUDENT’S PERCEPTION IN ONLINE LEARNING (A CASE STUDY ON SALUT KOTA KEDIRI) - Hafa, Mohammad Fauzi (Jurnal Pendidikan Bahasa Inggris Proficiency, 2023)
The aim of this study is to describe the students’ perception of SALUT Kota Kediri in online learning and to find out the obstacles faced by the students while doing online learning. This research used qualitative approach. The subject of this research was the 24 students of SALUT Kota Kediri who has taken the Strategi Pembelajaran Subject. The results showed that the students’ of SALUT Kota Kediri has the negative perception. And the obstacles faced by the students while doing online learning were no direct explanation from tutor, difficult to understand the material easily, technical issue and internet quota or signal sometimes trouble.